2, 6‐Diisopropylanilinium Bromobismuthates. Issue 4 (23rd December 2016) - Pandey, Souvik; Nair, Anju; Andrews, Alex P.; Venugopal, Ajay
Abstract : A systematic approach to obtain bromobismuthates with various bismuth/halide ratios stabilised by 2, 6‐diisopropylanilinium cations [ArNH3 ] (Ar = 2, 6‐diisopropylphenyl) is presented. New bromobismuthate compounds [(ArNH3 )(BiBr4 )]∞ (1 ), [(ArNH3 )3 (Bi2 Br9 )]∞ (2 ), [(ArNH3 )3 (BiBr6 )] (3 ) and [(ArNH3 )4 (BiBr6 )(Br)] (4 ) with Bi/Br ratios of 1:4, 1:4.5, 1:6 and 1:7 have been isolated and structurally characterised. [Bi2 Br9 ]∞ is a new structural motif in halobismuthate chemistry. In all the compounds, extensive hydrogen bonding is observed between the bromobismuthate moiety and the 2, 6‐diiosopropylanilinium cation, thus stabilising the inorganic–organic hybrid structures. Preliminary optical spectroscopic studies indicate that the optical band gap can be tuned by controlling the bismuth/halide ratio, which results in different dimensionalities in the halobismuthate structure. The compounds exhibit thermal stability up to 250 °C. Abstract : A systematic approach to obtain bromobismuthates with specific bismuth/halide ratios stabilised by a 2, 6‐diisopropylanilinium cation is presented.